Counselor Code of Ethics: Professional Responsibilities and Client Rights - Fitrianingsih, Fitrianingsih; Jaudah Jahro, Zalfa; Nahdiatun Nisa, Nida; Salsabila, Rifdah (Side: Scientific Development Journal, 2024)
The purpose of this study is to explain the rights of counselees and the responsibilities of counselors that must be fulfilled in accordance with the existing counselor code of ethics. The counselor code of ethics is a guide to professional behavior, a moral foundation, a collection of principles or values regarding morals in counseling practice. The results of this discussion explain that this code of ethics establishes ethical obligations for ABKIN members and provides guidelines for ethical practice of professional counselors or guidance and counseling teachers. Counseling ethics must involve awareness and desire to maintain the importance of the responsibility to protect client trust. The rights of counselees must be respected and protected by counselors, including the right to privacy, information, participation, and the right to receive quality services. Counselor responsibilities include the obligation to maintain confidentiality, avoid conflicts of interest, pay attention to client interests, and update professional knowledge and skills regularly. The counselor code of ethics aims to be a guide to behavior, helping to develop counseling services. The purpose of this study is to explain the counselor's rights and the counselor's responsibilities that must be fulfilled in accordance with the existing counselor code of ethics. The counselor's code of ethics is a guide to professional behavior, a moral foundation, a collection of principles or values relating to morals in counseling practice. The results of this discussion explain that this code of ethics establishes ethical obligations for ABKIN members and provides guidance on the ethical practice of professional guidance and counseling counselors or teachers. Counseling ethics must involve an awareness and a desire to maintain the importance of the responsibility to protect the client's trust. The counselor's rights must be respected and protected by the counselor, including the right to privacy, information, participation, and the right to quality services. The counselor's responsibilities include the obligation to maintain confidentiality, avoid conflicts of interest, look out for the client's interests, and update professional knowledge and skills on a regular basis. Counselors' code of ethics aims to be a guide to behavior, assisting in developing counseling services.